If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.4285714286x + 3 + -1x + 3 = 2 Reorder the terms: 3 + 3 + 0.4285714286x + -1x = 2 Combine like terms: 3 + 3 = 6 6 + 0.4285714286x + -1x = 2 Combine like terms: 0.4285714286x + -1x = -0.5714285714x 6 + -0.5714285714x = 2 Solving 6 + -0.5714285714x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -0.5714285714x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + -0.5714285714x = 2 + -6 -0.5714285714x = 2 + -6 Combine like terms: 2 + -6 = -4 -0.5714285714x = -4 Divide each side by '-0.5714285714'. x = 7 Simplifying x = 7
| 3k-1/3=4/9 | | [p+3]=10 | | [x+5]-2=6 | | 19-6(5x-4)=-5 | | 5=.86x | | x^4+21x^2=0 | | -2.6x=42.64 | | 9x+5=9(x-2) | | 6(2x-2)=-8(x+4) | | 3x-9=3(x-4) | | 4xsquared-3x+1=0 | | 4.1y=8.2 | | 2/3x-1/7=4/5 | | 2/3m-1/7=4/5 | | 4y-2=2y+4 | | 2c-14=4c | | a(5x-6)=-45x+54 | | -9x-12x=84 | | .20x+.82=-.13x+3.34 | | 7+3(x+2)=4(x-7) | | -6b=-36 | | 7x-13+5x=2x-11 | | .2x+.82=-.13x+3.34 | | (36/(x+3))-(15(x+9))=1 | | (8/x)-1=8/(x-1) | | 36-91d-78-5d+3+6d= | | 9+m=26 | | n/12=10 | | sqrt(x-2)=9 | | .06/12= | | x=-5x^2-2x+16 | | 2r+2=5x-11 |